To Be Led Astray? : The Effects of the 1881 Liquor Act on the Leiden Alcohol Trade - Schmidt, Ariadne; Van Oosten, Roos; Theerens, Astrid (TSEG - The Low Countries Journal of Social and Economic History, 2022)
The Dutch Drankwet (hereinafter: Liquor Act) of 1881, the result of decades of temperance activism, was met with much criticism — little had come of the national legislation’s aim to reduce the consumption of alcohol. Even so, did this also mean that little changed in the sale of alcohol? This article examines how the Liquor Act was implemented locally in Leiden and what impact this had on the sale of alcohol there. To this end, both city council minutes and patent registers are analyzed. Patent registers served as compulsory patent taxes and as licenses for liquor stores and drinking establishments. They provide valuable insight into the variation within the sector for alcohol sales in Leiden throughout the nineteenth century. Our examination shows that, contrary to the criticism of the law, the Liquor Act had both short- and long-term effects on Leiden’s pubscape. It led to a limited decrease in the number of public houses and primarily affected the smallest public houses, often owned by women.